Behavioral Labeling: Prompting Consumer Behavior Through Activity Tags - Fritze, Martin P.; Völckner, Franziska; Melnyk, Valentyna (Journal of Marketing, 2024)
This research introduces behavioral labeling as the use of names or tags that reflect an associated activity, and it proposes that this can induce corresponding behavior. Contrary to the common intuition that descriptions of behaviors emerge as markings for popular actions (i.e., the label is a consequence of the behavior), the authors propose that a description itself might also induce the corresponding action (i.e., the label is an antecedent of the behavior). Building on linguistic relativity theory and based on five studies conducted in the lab and field, the authors show that merely attaching a fictitious name to a behavior can induce that very behavior. The authors also explore a potential explanation for this finding by showing that a behavioral label can evoke mental imagery regarding the associated behavior, which enhances the implementation of the behavior. The results contribute to marketing theory by introducing behavioral labeling and highlighting how language can shape behaviors. Marketers can use behavioral labels to promote their offerings based on the associated behaviors, while public policy makers can use behavioral labels to encourage prosocial and proenvironmental behaviors.